ANALISIS SISTEM LEMBAGA KEUANGAN SYARIAH DAN LEMBAGA KEUANGAN KONVENSIONAL - Syauqoti, Roifatus; Ghozali, Mohammad (IQTISHODUNA, 2018)
For holding the banking system, Indonesia applied dual banking system based on institutional regulation Number 10, 1998. The existence of dual banking system was realized by monetary crisis on 1998, that caused bankrupt impact of conventional banking system for the high ratio of the debt interest. Dual banking system means that Indonesia applied both sharia and conventional banking system. For this matter we use qualitative method and analysis descriptive method, by describing and analyzing sharia financial foundation and conventional financial foundation system. both are same in money receiving technic, transfer mechanism, computer technology, and general terms to obtain the credit. Both sharia financial foundation and conventional financial foundation have more differences. The main different between them is in the profit gaining system obtain. Sharia bank applied profit sharing system which is oriented for blessed life here and the day after, in other case conventional bank applied interest system which is oriented for gaining profit as much as possible in this world. Moreover, sharia bank is watched by the sharia supervising council, in order to revive the pure sharia, not same as conventional bank.